Chemical etching of Sb2Se3 solar cells: surface chemistry and back contact behaviour. (1st October 2019) - Shiel, Huw; Hutter, Oliver S; Phillips, Laurie J; Turkestani, Mohammed Al; Dhanak, Vin R; Veal, Tim D; Durose, Ken; Major, Jonathan D
Abstract: The effect of (NH4 )2 S and CS2 chemical etches on surface chemistry and contacting in Sb2 Se3 solar cells was investigated via a combination of x-ray photoemission spectroscopy (XPS) and photovoltaic device analysis. Thin film solar cells were produced in superstrate configuration with an absorber layer deposited by close space sublimation. Devices of up to 5.7% efficiency were compared via current–voltage measurements ( J–V ) and temperature-dependent current–voltage ( J – V – T) analysis. XPS analysis demonstrated that both etching processes were successful in removing Sb2 O3 contamination, while there was no decrease in free elemental selenium content by either etch, in contrast to prior work. Using J – V – T analysis the removal of Sb2 O3 at the back surface in etched samples was found to improve contacting by reducing the potential barrier at the back contact from 0.43 eV to 0.26 eV and lowering the series resistance. However, J – V data showed that due to the decrease in shunt resistance and short-circuit current as a result of etching, the devices show a lower efficiency following both etches, despite a lowering of the series resistance. Further optimisation of the etching process yielded an improved efficiency of 6.6%. This work elucidates the role of surface treatments in Sb2 Se3 devices and resolves inconsistencies in previously published works.